2019
DOI: 10.3390/healthcare7040138
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Linkages among Economic Development, Energy Consumption, Environment and Health Sustainable in EU and Non-EU Countries

Abstract: There is a close and important relationship between environmental pollution and public health, and environmental pollution has an important impact on the public health. This study employed the two-stage meta-frontier dynamic network data envelopment analysis (TMDN-DEA) model to explore the environment pollution effects from energy consumption on the mortality of children and adult, tuberculosis rate, survival rate and health expenditure efficiencies in 28 EU countries and 53 non-EU countries from 2010 to 2014.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…The impact of air pollution on children's health has also been widely examined. For example, Feng et al [14] employed a two-stage meta-frontier dynamic network DEA (TMDN-DEA) model to explore the influence of energy consumption and the associated environmental pollution on the mortality of children and adults in 28 EU countries and 53 non-EU countries from 2010 to 2014, Lee et al [24] used a generalized additive model (GAM) time series analysis to explore the effect of multiple air pollutants (sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), ozone (O 3 ), carbon monoxide (CO) and aerodynamic diameter (PM 10 )) on the health of the children under 15 years old in Seoul from 1997 to 1999, and found that nitrogen dioxide and ozone were the main contributors to childhood asthma. In more recent research, Chen et al [6] found that PM 2.5 and PM 10 affected the health and lung function of primary school children, Fioravanti et al [15] found that traffic air pollution had no effect on childhood obesity in children aged 4 and 8 years in Rome, and Knibbs et al [22] found that exposure to outdoor NO 2 affected the respiratory systems of children aged 7-11 in Australia.…”
Section: Impact Of Air Pollution On Human Healthmentioning
confidence: 99%
See 4 more Smart Citations
“…The impact of air pollution on children's health has also been widely examined. For example, Feng et al [14] employed a two-stage meta-frontier dynamic network DEA (TMDN-DEA) model to explore the influence of energy consumption and the associated environmental pollution on the mortality of children and adults in 28 EU countries and 53 non-EU countries from 2010 to 2014, Lee et al [24] used a generalized additive model (GAM) time series analysis to explore the effect of multiple air pollutants (sulfur dioxide (SO 2 ), nitrogen dioxide (NO 2 ), ozone (O 3 ), carbon monoxide (CO) and aerodynamic diameter (PM 10 )) on the health of the children under 15 years old in Seoul from 1997 to 1999, and found that nitrogen dioxide and ozone were the main contributors to childhood asthma. In more recent research, Chen et al [6] found that PM 2.5 and PM 10 affected the health and lung function of primary school children, Fioravanti et al [15] found that traffic air pollution had no effect on childhood obesity in children aged 4 and 8 years in Rome, and Knibbs et al [22] found that exposure to outdoor NO 2 affected the respiratory systems of children aged 7-11 in Australia.…”
Section: Impact Of Air Pollution On Human Healthmentioning
confidence: 99%
“…Most of the above research only focused on one or two aspects, with no studies having analyzed the relationships between economic development, energy, environmental pollution and human health. Therefore, to fill this gap, the method proposed in Feng et al [14] was used to develop a modified Undesirable Meta Dynamic Network DEA model to examine the economic development, energy, environmental pollution and human health efficiencies in 31 Chinese cities in China, identify the regional differences, and provide suggestions for improvement.…”
Section: Literature Review Summarymentioning
confidence: 99%
See 3 more Smart Citations